De novo malignancy risk in patients undergoing the first percutaneous coronary intervention: A nationwide population-based cohort study. (15th August 2020) - Kwak, Soongu; Choi, You-Jung; Kwon, Soonil; Lee, Seo-Young; Yang, Seokhun; Moon, Inki; Lee, Hyun-Jung; Lee, Heesun; Park, Jun-Bean; Han, Kyungdo; Kim, Yong-Jin; Kim, Hyung-Kwan
Abstract: Background: Although percutaneous coronary intervention (PCI) has been the mainstay of revascularization strategy for significant coronary artery disease, future cancer risk after PCI has never been explored. We aimed to investigate the risk of incident cancer in patients undergoing PCI for the first time. Methods: We studied 125, 613 patients who underwent the first PCI between 2010 and 2015 without a prior history of cancer. For comparison, we selected 628, 065 age- and sex-matched controls without any history of cancer or PCI who completed the assigned national health examination during the same period. Results: During a median 4.56 years (interquartile range, 3.06–6.13 years), 8528 patients from the PCI group and 40, 166 controls were newly diagnosed with cancer (incidence rate, 15.1 vs. 13.9 per 1000 person-years, p < 0.0001). Patients undergoing PCI presented a higher risk for cancer development than the controls in multivariable Cox analysis (adjusted HR [aHR] 1.06, 95% CI 1.04–1.09, p < 0.0001). To minimize potential surveillance bias, we performed 1-year lag analysis by eliminating participants who developed cancer within 1 year from the PCI. In this analysis, the increased risk of overall cancer in the PCI group became insignificant (aHR 1.02, 95% CI 0.99–1.05, p = 0.2017). Regarding site-specific cancers, however, the risk of lung and hematologic malignancies remained higher and the risk of gastrointestinal, liver/biliary/pancreas, thyroid, and breast cancers remained lower in the PCI group. Conclusions: Differential future cancer risks were observed in patients undergoing PCI. The results suggest that specialized surveillance strategy might be warranted for this expanding population. Highlights: Patients undergoing PCI carry a differential de novo malignancy risk. Particularly, the risk of lung and hematologic malignancies was significantly increased. The specialized surveillance strategy might be warranted for this population.